Politik Hukum Pemberantasan Prostitusi Online Terkait Kriminalisasi Pekerja Seks Komersial dan Pengguna - I Dewa Gede Dana Sugama; Diah Ratna Sari Hariyanto (Fakultas Hukum, Universitas Warmadewa, 2021)
Prostitution cases have emerged as a phenomenon having continuously loaded with law enforcement actions in Indonesia; the modus operandi is getting developed over time. The case that is currently trending is the case of online prostitution. Although prostitution cases have been set forth in the Criminal Code and online transaction-related legal provisions can be found in the Electronic Information and Transaction Law (ITE Law), however, online prostitution cases are in fact difficult to eradicate. This is due to the condition that only the procurers or procuresses can be held liable for the acts, while sex workers (commercial sex workers) and the online prostitution service users cannot. This indicates that the prostitution-related legal arrangement needs to be reconstructed, and for that, the present study has an urgent force to be carried out to review the online prostitution regulations as well as the legal politics to eradicate prostitution, particularly regarding the criminalization of sex workers (commercial sex workers) and the online prostitution service users. This study applies a normative law research method design. The results of the study show that the Criminal Code does not regulate the conviction of commercial sex workers and online prostitution service users, so they cannot be held criminally liable for the act. If the online prostitution-related regulations outside those in the Criminal Code are examined further, sex workers and their service users can be charged with the ITE Law, but the rule is still general in nature - regulating prohibitions that violate decency. Regulations on prostitution can also be found in Regional Regulations (Perda), but not all regions have or issue the regulations on Prostitution, so their enforcement is limited to the territory. The political law that can be learned from this fact is the reform of criminal law through the synergy of the draft of Criminal Code concept through criminalization and the provision of criminal threats against commercial sex workers and the online prostitution service users so that they can be held criminally liable for (penalization).